Development of educational games for learning waste management. Issue 3 (March 2021) - Satria, E; Fitriani, L; Muhsin, Y S; Tresnawati, D
Abstract: The waste problem is caused by people's behaviour that does not care about environmental cleanliness. This study aims to create an Android-based game education application as a means to educate the public in managing waste. The method used is the multimedia development life cycle, consisting of concept, design, material collecting, assembly, testing and distribution. The results of the study are in the form of the design and development of edugame applications on waste classification, targeting primary school children. The edugame design consists of 3 levels, adapted to the classification of waste types: organic, non-organic and toxic. The application is built on the Android platform with the concept of an adventure game that provides users with real-world experience in managing waste properly. Edugame application is expected to be an alternative in learning to the community in maintaining environmental cleanliness.